Flexible Nasopharyngolaryngoscopy for the Assessment of Upper Airway Disorders - Regmi Chalise, Sangita; Khadka, Subash (Nepalese Medical Journal, 2018)
Introduction: Upper airway problems are frequently encountered in ENT practice. It is difficult to diagnose upper airway pathology by conventional methods. So use of fibreoptic flexible nasopharyngoscopy (NPL) is very helpful in both diagnosis and treatment of upper airway disorders. The aim of this study is to observe the usefulness of flexible NPL in patients with upper airway problems as an outpatient procedure. Materials and Methods: A cross sectional descriptive study was conducted in the department of ENT at KIST medical college teaching hospital during the period of 2years. A total of 138 patients who had persistent upper airway symptoms and underwent NPL were included in the study Detail history, clinical examination and required investigations were done. Data were recorded and analysed. Results: Total 138 patients suffering from upper airway disorders underwent NPL. Among them 65(47.1%) were males and 73(52.9%) were females. Age range was from 16 to 82 years. Most common problem observed was laryngopharyngeal reflux disease accounting for 41 percent of cases followed by vocal cord nodule and polyp. Conclusions: Flexible fiberoptic nasopharyngolaryngoscopy (NPL) is safe and noninvasive outpatient department procedure for the assessment of upper airway disorders.